Stock market reaction towards change of Malaysian government - Mohamad Annawi, Anuar (2021)
This study examines the effect of change of government on the Malaysian stock market for the last five years. The empirical model used in this study are abnormal return which calculated using three most-used method in research which are mean-adjusted model, market-adjusted model and market model. This method is used to investigate the abnormal return of the stock market of the FTSE Bursa Malaysia KLCI on before-event and after-event of two most important political announcement that happen in Malaysia for the last 5 years, which is the 13th General Election in 2018 and change of Malaysian Government happen in 2020. The selection of these event of interest is to study whether important political announcement causing any significant abnormal return on stock market which can be relate with the efficient market hypothesis (EMH) that was presented by Markowitz (1952) and Fama (1970). Generally, results from statistical analysis uncover that there is no significant abnormal return before the 2018 General Election and before the change of Malaysian government in 2020. However, there is statistically significance negative abnormal return observed on the after-event window, which is after general election in 2018, and after the change of government in 2020. The major implication of these findings is that political risk which related to political uncertainty and political instability may causing the stock market to become instable and causing the trust deficit among investors.